Art and music : a student's guide - Munson, Paul Allen (Wheaton, Illinois : Crossway, 2014)
God made us to enjoy beauty wherever we find it, whether it’s music or the visual arts. But sin finds ways to obscure what is right in front of our eyes and ears. Drawing on years of teaching experience, two professors offer tips for understanding, evaluating, and appreciating art in all its forms while highlighting the important ways in which art and music reflect the glory of God. This book will help you better understand and appreciate humanity’s pursuit and imitation of beauty through artistic expression—a vital means by which we bear witness to the beauty of our Creator.
What do we mean by the word beauty? -- Why should we enjoy art and music? -- How do we judge art and music? -- Looking at art -- Listening to music.
Keywords: Christianity and the arts; Aesthetics -- Religious aspects -- Christianity; Christianity and art; Music -- Religious aspects -- Christianity